Biological activities of leaf extracts from selected Kalanchoe species and their relationship with bufadienolides content. (1st January 2020) - Stefanowicz-Hajduk, Justyna; Hering, Anna; Gucwa, Magdalena; Hałasa, Rafał; Soluch, Agata; Kowalczyk, Mariusz; Stochmal, Anna; Ochocka, Renata
Abstract: Context: Kalanchoe species (Crassulaceae) are widely used in traditional medicine as remedies in infectious diseases and cancer treatment. Objective: Cytotoxic and antimicrobial activities of Kalanchoe daigremontiana Raym.-Hamet & H. Perrier, K. pinnata (Lam.) Pers., and K. blossfeldiana Poelln. extracts were determined. The relationship between biological activities and the extracts bufadienolides content was also investigated. Materials and methods: Fresh leaves of Kalanchoe species were macerated with 95% ethanol or water. The quantitative analysis of bufadienolides in the extracts was carried out with mass spectrometry. Cytotoxicity tests were performed on human cancer cell lines – HeLa, SKOV-3, MCF-7, and A375 by MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) assay and Real-Time Cell Analysis system. The microbiological study was done using a few bacteria strains (β-hemolytic Streptococcus, Corynebacterium diphtheriae, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus hirae, Escherichia coli ) and Candida albicans . Results: The K. blossfeldiana ethanol extract and K. daigremontiana water extract exhibited the most potent cytotoxic activity (IC50 < 19 µg/mL for HeLa and SKOV-3 cells). The strongest antibacterial effects showed ethanol extract of K. blossfeldiana and K. pinnata (MIC values were 8.45, 8.45, 0.25 and <33.75 µg/mL for S. aureus, S. epidermidis, and E. hirae, respectively). The highest total amount of bufadienolides was in K. daigremontiana ethanol extract. In contrast, K. blossfeldiana ethanol extract did not show the presence of these compounds. Conclusions: Kalanchoe blossfeldiana ethanol extract is a potential candidate for cancer and bacterial infection treatment. Additionally, the biological effects of Kalanchoe extracts are not dependent on the presence and amount of bufadienolides in the plant extracts.